Behavioral patterns in university students: a study with a humanistic approach - Fierros, Clara Alejandra Beltrán; Pérez, Carmen Estela Fierros; Bernal, José Antonio Soto; Gómez, Jesús Francisco Ramírez; Aguilar, José Aurelio Cortina; Graciano, Milton López; Castro, Luz María López (Technium Education and Humanities, 2025)
This study employs a mixed-methods approach, utilizing the Aggression Questionnaire (AQ) by Buss and Perry (1992) and interviews. The sample consisted of 89 university students from four different academic levels, who completed the questionnaire. Subsequently, interviews were conducted with one student and with several teachers. The results indicated that verbal aggression was present in 83% of female students and 80% of male students. Physical aggression was more prevalent among male students (71%) than female students (67%). Regarding anger, it was found in 63% of female students and 54% of male students, while hostility was observed in 62% of female students and 58% of male students. The student interview highlighted instances of aggressive behavior towards both peers and teachers. The teacher interviews revealed some common characteristics of aggressive behavior among students. These findings motivated the development of a pedagogical intervention proposal based on a humanistic approach, with the aim of improving student behavior and attitudes.